Self-evaluative practices to enhance e-pedagogy - Raistrick, Claire (Proceedings of the International Conference on Networked Learning, 2014)
New technologies and an evolving higher education landscape create pedagogical challenges for educators. This environment demands e-pedagogy — the capacity of technology to satisfy real learning which bolsters the student experience. However, how can educators be supported to make the cultural shift necessary to embrace technology in convincing ways? This social practice research draws alongside seven educators studying a postgraduate award in e-learning in academic and professional practice at an English university. Educators who are making and evaluating a technology enhanced learning innovation. The study’s rather unusual object is their self-evaluative practices and knowledge on this is co-constructed via dialogical conversations with participants. The significant output is a series of seven typologies built-up around RUFDATA, an established evaluatory framework with seven categories: reasons and purposes, uses, focus, data and evidence, audience, timing and agency. Substantial new knowledge of how educators do self-evaluation when making a technology enhanced learning innovation in higher education is created. This knowledge is about constellations of routine behaviours; behaviours which seek out value and are themselves intrinsically worthwhile. Collectively known as SEPT4TEL (self-evaluative practices typologies for technology enhanced learning), these 25 guiding principles depict self-evaluative practices and are promoted to educators seeking guidance on pragmatic ways to enhance their e-pedagogy. Evaluation is about judgements and it is the attribution of worth which distinguishes self-evaluative practices from other deliberative ways educators explore their professional practice, like reflection and action research. Self-evaluative practices are promoted as a foil to academics’ tendency to adopt their pedagogy uncritically, simply merging it with habitual institutional practices. In this paper the introduction and research methods are followed by an exposition of self-evaluative practices which forms the main part of this paper. Numerous quotations illustrate how dialogical conversation leads to the SEPT4TEL framework. For example, the transformational effect of ’evaluative creep’ on change processes and its ability to advance educators’ competence is profiled. Ultimately, self-evaluators become ’carriers’ of practices as they knowingly or unknowingly exert a bottom-up influence on the use and effectiveness of technology for learning. I conclude that self-evaluative practices can benefit use of new technologies for learning and recommend the SEPT4TEL framework to educators seeking to improve connections between technology and learning. Indeed, a sufficient constellation of self-evaluative practices is potentially powerful in a sociocultural sense, acting as a catalyst — with the power to leverage more widespread change.